Biogenic silver nanoparticles (AgNPs) from Tinosporacordifolia leaves: An effective antibiofilm agent against Staphylococcus aureus ATCC 23235 - Ghosh, Sreejita; Mondol, Somdutta; Lahiri, Dibyajit; Nag, Moupriya; Sarkar, Tanmay; Pati, Siddhartha; Pandit, Soumya; Alarfaj, Abdullah A.; Mohd Amin, Mohamad Faiz; Edinur, Hisham Atan; Ahmad Mohd Zain, Muhammad Rajaei; Ray, Rina Rani (Frontiers in Chemistry, 2023)
Medicinal plants are long known for their therapeutic applications. Tinospora cordifolia (commonly called gulancha or heart-leaved moonseed plant), a herbaceous creeper widely has been found to have antimicrobial, anti-inflammatory, anti-diabetic, and anti-cancer properties. However, there remains a dearth of reports regarding its antibiofilm activities. In the present study, the anti-biofilm activities of phytoextract of T. cordifolia and the silver nanoparticles made from this phytoextract were tested against the biofilm of Staphylococcus aureus, one of the major nosocomial infection-producing bacteria taking tetracycline antibiotic as control. Both phytoextract, and the biogenic AgNPs, were found successful in reducing the biofilm of S. aureus. The biogenic AgNPs formed were characterized by UV- Vis spectroscopy, Field emission Scanning Electron Microscopy (FE- SEM), and Dynamic light scattering (DLS) technique. FE- SEM images showed that the AgNPs were of size ranging between 30- 50 nm and were stable in nature, as depicted by the zeta potential analyzer. MIC values for phytoextract and AgNPs were found to be 180mg/ ml and 150 µg/ ml against S. aureus respectively. The SEM analyses clearly indicated that although the phytoextracts could destroy the biofilm network of S. aureus cells yet the biogenically synthesized AgNPs were more effective in biofilm disruption. Fourier Transformed Infrared Radiations (FT- IR) analyses revealed that the AgNPs could bring about more exopolysaccharide (EPS) destruction in comparison to the phytoextract. The antibiofilm activities of AgNPs made from the phytoextract were found to be much more effective than the non-conjugated phytoextract, indicating the future prospect of using such particles for combatting biofilm-mediated infections caused by S aureus.